Morphological variation of the Long-tailed Reed Finch Donacospiza albifrons (Vieillot, 1817) (Aves: Thraupidae) - Lopes, Leonardo Esteves (Zootaxa, 2017)
The Long-tailed Reed Finch Donacospiza albifrons of south-central South America is patchily distributed in a variety of open habitats, usually near water. I present a detailed study of morphological variation based on 141 specimens, describing its plumage sequence and presenting notes on its molt and breeding. The Long-tailed Reed Finch shows no sexual dichromatism, but males average longer-winged than females. The species shows three distinct age-related plumages, which are redescribed here. It also shows marked individual variation in plumage and size, also showing marked plumage variation due to feather wear. Geographic variation is also marked, with birds from dry grasslands in northern highlands typically being larger, paler, and less streaked than birds from wet grasslands in southern lowlands, but there at some exceptions to this geographic pattern. I conclude that there is no solid basis for splitting the species into two or more taxa, and suggest considering the Long-tailed Reed Finch as a single, highly polymorphic species.